Idosos e internet: mediações nos usos de serviços bancários digitais - SIMÕES, Camila de Andrade (Universidade Federal do Pará, 2019)
In a context of internet popularization, mainly through mobile devices, digital inclusion is an expression linked to democracy using such means. Among the socalled excluded groups, the elderly person is noticed and the problematization follows in the instrumentalized interaction relation that maintains with private companies and the connected devices that circulates. It is worth mentioning the worldwide aging, the same with Brazilian population, as well as the timid finding towards elderly digital literacy - from academic to domestic. Ahead it was believed that it was necessary to look closely at a technological actor who presented considerable proximity to Brazilian society in general. Thus, the financial institution was selected because it represents the one through which a capital company performs its main transactions, constant and obligatory (receipts and payments). It is a type of social actor that has in its history, intimate connection with the technological and communication advances, wich involves, today, most of midia services. Thus, two social actors with different interests are placed face to face, in order to verify this relationship from the reception. So, as a central objective, seeks to understand the senses produced by the elderly person in digital banking. Specifically, (1) to verify the relationship between the elderly group of persons investigated and the institution, (2) to identify which devices are most used by the elderly and the banks for this purpose, and (3) to seek to understand which factors the uses that the elderly make of such services and devices. As a methodological proposal, the semi-structured interview, applied to the elderly groups, and the direct observation of digital inclusion courses offered to elderly people in the city center of Belém do Pará, Brazil, were selected. The results indicate little or no use of banking applications by the elderly person investigated. Among those who use it, delivery and trust are less restricted. Among those who do not use baccalaureate applications, insecurity in processes and in themselves, and the lack of knowledge about digital media in general seem to prevent them from pursuing it. In most, the elderly person prefers procedures in physical agencies. Even if directed to use connected applications and digital devices (ATMs or even smatphones) by banking agents, other factors are among the appropriations of these devices by the elderly person.